(3cJGH aj GdMOjKs - (3Ydj Hf GdMSjf Hf Ydj GdeDOH Hf GdUHGZs
(3ChdgG (B:s
(3MOKfG CHh GdYHGS CMeO Hf Ydi bGd QShd Gddg Udi dGdg Ydjg hSde (B:_ (3GdYde NRGFf heaJGMg dSDGd aSdhG jQMece Gddg aEfg jDLQ ajg CQHYI GdSGFd hGdeJcde hGdeSeY hGdeMH dge s
(3BNQgG (B:s
(3Yf Cgd gPG GdHjJ aeG dG CJgec dgi Gdbhe hJaQbhG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B_ (3GdfLa (B(369) s
Keywords: (3GdeLGejYs